ISOLASI SENYAWA AKTIF DARI LABAN (VITEX PINNATA) TUMBUHAN OBAT ASLI KALIMANTAN TIMUR DAN KALIMANTAN UTARA SEBAGAI BAHAN KOSMETIK - Purba, Ritson; Azizah, Amanda Salwa Nur; Maulidawati, Rista (PROSIDING SEMINAR KIMIA, 2024)
Laban (Vitex pinnata), a natural medicinal plant of East and North Kalimantan, was the subject of an isolation process to produce active chemicals. This study uses a chromatography column with a solvent gradient system to carry out the fractionation or isolation process. The crude plant extract is first fractionated using a solvent with the least polarity, n-hexane, and then additional solvent is added. The goal is to ascertain the anti-bacterial and antioxidant activity of plant isolates as well as obtain pure compounds and describe the properties and structure of isolated compounds. Previously, an extract known as Laban (Vitex pinnata) extract was utilized. This plant was isolated, and the isolation yield for Laban (Vitex pinnata) was 85.06%. The chromotography column for Vitex pinnata is done by mixing a sample of 10 grams of Vitex pinnata leaf extract with a 37.5 gram sample of silica and then inserting it into the saturated chromotography column. The isolates were tested for their antioxidant activity and anti-bacterial P.acne (anti-acne). Test of antioxidant were determined by their antioxidant activity through the DPPH free reduction mechanism with 3 repetitions control. The test was using a UV-Vis spectrophotometer at a temperature of 25°C with a wavelength of 514 μm. Keywords: isolation, antioxidant, P.acne bacteria, cosmetics.